Energy-effective issue logic - Folegnani, Daniele; González, Antonio (Proceedings of the 28th annual international symposium on Computer architecture, 2001)
The issue logic of a dynamically-scheduled superscalar processor is a complex mechanism devoted to start the execution of multiple instructions every cycle. Due to its complexity, it is responsible for a significant percentage of the energy consumed by a microprocessor. The energy consumption of the issue logic depends on several architectural parameters, the instruction issue queue size being one of the most important. In this paper we present a technique to reduce the energy consumption of the issue logic of a high-performance superscalar processor. The proposed technique is based on the observation that the conventional issue logic wastes a significant amount of energy for useless activity. In particular, the wake-up of empty entries and operands that are ready represents an important source of energy waste. Besides, we propose a mechanism to dynamically reduce the effective size of the instruction queue. We show that on average the effective instruction queue size can be reduced by a factor of 26% with minimal impact on performance. This reduction together with the energy saved for empty and ready entries result in about 90.7% reduction in the energy consumed by the wake-up logic, which represents 14.9% of the total energy of the assumed processor.